Direct Conversion of Cellulose into Alkyl Glycoside Surfactants. Issue 8 (14th March 2017) - Puga, Alberto V.; Corma, Avelino
Abstract: The one‐step production of biodegradable alkyl glycoside (1‐dodecyl mono‐ and oligoglucoside) surfactants from cellulose has been achieved by direct alcoholysis in fatty alcohol media under Brønsted acid catalysis at near‐ambient pressure. The fatty alcohol serves as both solvent and reagent. Addition of small amounts of water prevents dehydration events and thus minimises product and solvent degradation. Furthermore, high initial cellulose loadings and short thermal cycles enable moderate‐to‐high conversions and selectivities (up to ≈ 70 %), and low solvent‐to‐product ratios. Abstract : The direct production of biodegradable alkyl glycoside surfactants from cellulose in a single step has been achieved in fatty alcohol media under Brønsted acid catalysis at near‐ambient pressure; addition of small amounts of water and short thermal cycles enable moderate‐to‐high conversions and selectivities (up to ≈ 70 %), and low solvent‐to‐product ratios.